The financial crisis and corporate debt maturity: The role of banking structure - González, Víctor M. (Journal of corporate finance (Amsterdam, Netherlands), 2015)
This paper analyses the influence of the financial crisis on corporate debt maturity for 39 countries during the period 1995–2012. The results reveal the importance of the dependence of firms on external finance and the banking structure of the countries on debt maturity during the financial crisis. Corporate debt maturity was found to decline during the financial crisis. However, only those firms that were more dependent on external finance before the onset of the financial crisis suffered this reduction. The reduction in corporate debt maturity is the result of a higher average increase in short-term debt than in long-term debt. The financial crisis had a stronger negative effect on corporate debt maturity in countries with less bank concentration, while the debt maturity of larger firms decreased less as a result of the financial crisis than the debt maturity of smaller firms in countries where banks play an important role in the financing of the private sector. •Corporate debt maturity was found to decline weakly during the financial crisis.•Evidence is consistent with the existence of a credit supply effect.•Bank concentration helps firms to avoid the reduction in debt maturity.•Smaller firms suffer more reductions in countries where the role of banks is greater.